Invasion characteristics and clinical significance of tumor-associated macrophages in gastrointestinal Krukenberg tumors - Huang, Zigao; Li, Baojia; Qin, Haiquan; Mo, Xianwei (Frontiers in Oncology, 2023)
Background: Tumor-associated macrophages (TAMs) have been used as a potential drug target in pre-clinical research and clinical trials of multiple cancer treatments. However, the regularities of its distribution in krukenberg tumors (KT) remain unclear. Our goal was to investigate the expression and prognostic value of TAMs in gastrointestinal malignancy patients with KT. Methods: Immunohistochemical staining was used to detect the infiltration of various types of TAMs in the surgical tissues of 35 KT patients. Based on the distance between TAMs and tumor cells, the infiltration level of TAMs in tumor nests (TN), tumor stroma (TS) and invasive margin (IM) area was evaluated. Kaplan-Meier method and univariate/multivariate Cox regression risk models were used to analyze the relationship between TAMs invasion degree and overall survival (OS) and progression-free survival (PFS). Results: TAMs has spatial heterogeneity distribution between TN, TS and IM regions in primary tumor (PT) and KT tissue. TAMs infiltrated in the TN were considered to have greater prognostic value and limited influence by preoperative neoadjuvant therapy, even though the grade of invasion between PT and KT tissue was similar. Moreover, CD68+TAMs in TN of KT tissue was an independent risk factor affecting patients' OS, while tumor resection scope might be an independent risk factor affecting patients' PFS. Conclusions: In view of the close relationship between TAMs and tumor microenvironment and patient prognosis, TAMs as a target drug combined with chemotherapy is expected to become a new idea for the treatment of patients with gastrointestinal malignancy complicated with KT.